Low-Dose Clonazepam Effect on Epileptiform Activity - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The effect of low-dose clonazepam (CZP) on 24-hour long-term EEG recordings in 15 children with epilepsy was evaluated at the Karolinska Hospital, Stockholm, Sweden.